The analysis of influence of temperature conditions of piston long-stroke compressor stage on thermodynamic efficiency of a heat pump - V. L. Yusha; A. Yu. Gromov; P. V. Ushakov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
A brief overview analysis of the applicability of heat pumps in various branches of engineering and production as one of the most energy-saving technologies is presented. The theoretical cycle of a heat pump based on a piston long-stroke low-speed compressor stage is considered, which allows to realize the compression process in a wide range of the polytrope index. The analysis of the relationship of the integral characteristics and energy efficiency of the heat pump with the temperature regime of the compressor stage when using water vapor as a working fluid is performed. The presented results of the theoretical analysis reflect the nature of the dependence of the thermal power and the transformation coefficient of the heat pump on the polytropy index of the compression process, boiling temperature, steam overheating at suction, the difference in condensation and boiling temperatures.